Gray's anatomy for students - Drake, Richard L.; Mitchell, Adam W. M.; Vogl, Wayne (Philadelphia, PA : Elsevier, 2020)
Easy to read, superbly illustrated, and clinically relevant, Gray's Anatomy for Students, fourth edition, is the medical student's go-to text for essential information in human anatomy. This fully revised volume focuses on the core information students need to know, in an easy-to-access format and with additional multimedia features that facilitate effective study and mastery of the material. Expert authors and global advisors share their extensive teaching and clinical experience, using more than 1000 carefully crafted, original illustrations throughout the text. -- From publisher's description.
The body -- Back -- Thorax -- Abdomen -- Pelvis and perineum -- Lower limb -- Upper limb -- Head and neck -- Neuroanatomy.
Includes index.
Keywords: Anatomy